The excitation and detection of a leaky surface electromagnetic wave on a high-index dielectric grating in a prism-coupler geometry - Simonsen, I.; Maradudin, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
A periodically corrugated interface between vacuum and a high-index dielectric medium supports a p-polarized leaky surface electromagnetic wave whose sagittal plane is perpendicular to the generators of the interface. This wave is bound to the surface in the vacuum region, but radiates into the high-index dielectric medium. We study the excitation of this wave by p-polarized light incident from a prism on whose planar base the high-index dielectric medium in the form of a film is bonded. The unilluminated surface of the film is periodically corrugated, and is in contact with vacuum. Peaks and dips in the dependence of several low-order diffraction efficiencies on the angle of incidence (Wood anomalies) are the signatures of the excitation of the surface wave.